IT IS NOT JUST A SONG FOR CHILDREN: A SEMIOTIC ANALYSIS - Martina Mulyani; Fathan, Aulia Mujahidah (English Education Department of STKIP Pasundan, 2024)
A Song is a good medium for children to learn about culture. Through songs, songwriters can convey their native culture, which they regard as valuable for future generations to inherit. There are several songs for children in Indonesia written by talented songwriters that portray the distinctive qualities of Indonesia’s culture. For the listeners to recognize the Indonesian virtues implied in the songs while simultaneously enjoying the songs, the songwriters demonstrated some strategies that allowed them to convey the intended culture. This study attempted to determine how songwriters managed to pass culture through songs and what culture they tried to convey. A semiotic analysis, including textual analysis, thematic progression, and sign analysis, was conducted on five popular songs for children from four well-known songwriters in Indonesia. The results showed that the songwriters utilized the material process to help the children visualize the content of the songs and used existential phrases and a variety of marked themes, including conditions, adjuncts, and dependent themes, to convey many key points in a single sentence. In addition, the songwriters also employed a combination of multiple thematic progressions to develop the subject, zigzag thematic development to maintain the text's logical relation, and reiterative thematic progression to emphasize the theme of the text. The findings are valuable as references, especially for those who wish to write music for young listeners